Formation conditions of noble metal mineralization in sulfide cobalt-copper-nickel ores of Kamchatka (on the example of Annabergitovaya Schel ore occurrence) - Roman M. Novakov; Valentina E. Kungurova; Svetlana V. Moskaleva (Записки Горного института, 2021)
The authors present research results, the purpose of which is to study the specifics of noble metal mineralization and its genesis in sulfide cobalt-copper-nickel ores of the Kamchatka nickel-bearing province. The paper is dedicated to one of its many ore occurrences called Annabergitovaya Schel (Annabergite Gap). The material composition of platinoid, silver, gold, bismuth and tellurium minerals, as well as sulfarsenides in the ores of this occurrence was investigated. Based on the data of mineral formation sequence and the use of geosensors, conclusions were drawn regarding the genesis of noble metal mineralization.